Comparison and analysis for prediction accuracy of true triaxial rock strength criterion - He, Shiwei; Cheng, Hong; Cheng, Lin; Yuan, Feiyu; Zhang, Mingming (Frontiers in Earth Science, 2024)
To verify the predictive accuracy of existing strength criteria on true triaxial strength experimental data, understand the characteristics of different strength criteria, and provide a basis for selecting strength criteria for engineering applications, ten commonly used rock strength criteria were selected and divided into MC and HB types. The distribution characteristics of the yield surfaces and yield curves of different criteria were compared and analyzed in the principal stress space and the π plane. Afterwards, based on the least absolutely deviation method, these ten strength criteria were used to predict 32 sets of true triaxial rock strength experimental data. The results showed that the range of undetermined parameters for MC type strength criteria was small and easy to determine, while the range of undetermined parameter for HB type criteria was large and difficult to determine the search range, in addition, the fitting process may not converge. The fitting accuracy of strength criteria for true triaxial experimental data depends on the sensitivity of rock strength to the intermediate principal stress. PH and GP criteria are the most sensitive to changes of the intermediate principal stress, followed by MWC and ML criteria, MGC and ZZ criteria, MCJP and HBWW criteria. PH and GP criteria overestimate the effect of the intermediate principal stress, resulting in the largest prediction errors, while the other three-dimensional strength criteria have high prediction accuracy and no significant differences. The research results can provide scientific basis for engineering design, geological hazard prediction, and mineral resource development.